Dynamic Event-Triggered Fault Detection via Zonotopic Residual Evaluation and Its Application to Vehicle Lateral Dynamics - Wang, Xudong; Fei, Zhongyang; Yan, Huaicheng; Xu, Yinliang (IEEE transactions on industrial informatics, 2020)
This article is concerned with the event-triggered fault detection problem for discrete-time systems subject to unknown-but-bounded (UBB) process disturbance and measurement noise via zonotope-based residual evaluation. To save communication resources, a novel discrete-time dynamic event-triggered mechanism is proposed. An optimal event-triggered l_1 /H_{∞ } fault detection observer (FDO) design criterion is proposed such that the generated residual is sensitive to system faults while robust against exogenous disturbance and measurement noise. On the basis of the designed FDO, a zonotope-based dynamic threshold for residual evaluation is well constructed by considering the impacts of disturbance, noise, and event-triggered communication. Finally, a vehicle lateral dynamic system is adopted to illustrate the effectiveness of the proposed zonotope-based dynamic event-triggered fault detection mechanism.